First report of Matryoshka RNA virus in an African-European migrant bird - Mélanie Duc; Carlos Esperanza; Carolina Romeiro Fernandes Chagas; Tatjana Iezhova; Ravinder N. M. Sehgal; Gediminas Valkiūnas (PLoS ONE, 2025)
Viruses are diverse biological entities found virtually in all environments on Earth. Their association with parasitic protozoans was shown in the late 1980’s, followed by evidence that these viruses can influence the treatment of infections as well as influence parasite virulence. Recently, Matryoshka RNA viruses (MaRNAV) were discovered in Plasmodium vivax infected patients in Malaysia, as well as in species of the closely related avian haemosporidian genera Leucocytozoon and Haemoproteus in Oceania and North America. However, they have not been reported in other continents so far. The aim of this study was thus to screen haemosporidian infected European birds (African migrants and residents) for the presence of MaRNAV. Whole blood samples from wild birds were collected in Lithuania in May 2023. Haemosporidian parasite infections were first assessed by microscopic examination and later confirmed via PCR. RNA was isolated and tested by Reverse Transcriptase (RT) PCR for the presence of MaRNAV. Of the 12 samples that were RT-PCR-positive, only one from a common whitethroat (Curruca communis) had a sequence with 63% similarity to MARNAV-2 found in Leucocytozoon infected birds from Oceania. Total RNA from this sample was sequenced, bioinformatically analyzed, and a new virus, MaRNAV-7, was identified. At the amino acid level, it is phylogenetically closely related to MaRNAV-2, MaRNAV-3 and MaRNAV-6 RdRp sequences, all found in Leucocytozoon infected birds. This is the first report of MaRNAV in an African-European haemosporidian infected bird, and a first step in understanding MaRNAV prevalence, distribution, and specificity. However, the effects that MaRNAV can have on the parasites, modulation of the host immune response and transmission rates remain unknown.